STUDI IN SILICO POTENSI SENYAWA TURUNAN KORTIKOSTEROID SEBAGAI OBAT COVID-19 - Ridho Pratama (Jurnal Veteriner Nusantara, 2020)
Compounds containing corticosteroids have anti-inflammatory effects and can also suppress the immune system to work effectively. The use of corticosteroid derivatives is limited because certain doses are very toxic to the body. With the development of science, the properties of absorption, distribution, metabolism, excretion, and toxicity or the so-called ADME-Tox of bioactive corticosteroid compounds can be predicted using in silico research methods, so as to minimize the use of test animals in in vivo studies. In addition, in silico can also predict bioactive corticosteroid compounds that can become receptor inhibitors of COVID-19. This study aims to determine the absorption, distribution, metabolism, excretion, and toxicity of corticosteroid derivatives and the interaction of COVID-19 receptors with corticosteroid derivatives in silico so that the potential of corticosteroid derivatives as drug candidates for COVID-19 can be predicted. The in silico analysis method uses the FAFDrugs web application and the UCSF Chimera software. The results showed that corticosteroid derivatives, namely methylprednisolone, and prednisolone, have good absorption, distribution, metabolism, excretion, and toxicity properties and have the same docking score and are close to the docking score of positive control compounds so that they have the potential to become a COVID-19 drug. This research requires a further in vitro and in vivo test phase as a step to validate the potential of the COVID-19 drug from methylprednisolone and prednisolone compounds.